Validation of the UPDRS section IV for detection of motor fluctuations in Parkinson's disease. (June 2016) - Raciti, L.; Nicoletti, A.; Mostile, G.; Bonomo, R.; Contrafatto, D.; Dibilio, V.; Luca, A.; Sciacca, G.; Cicero, C.E.; Vasta, R.; Zappia, M.
Abstract: Introduction: The UPDRS-IV represents the most common screening tool to assess motor fluctuations in patients with PD despite the lack of a clinimetric validation. Objectives: We evaluated sensitivity and specificity of UPDRS-IV using a 12-h waking-day motor assessment as the gold standard. Methods: We consecutively enrolled PD patients who underwent a 12-h waking-day motor assessment in the study. Patients were clinically evaluated every 2 h for 12 h using the UPDRS-III. Motor scores were reported as a line graph and six blinded raters classified patients as having or not having motor fluctuations. The UPDRS-IV was used in order to assess the presence of predictable and unpredictable motor fluctuations according to items 36–38. Results: Sixty two PD patients were enrolled in the study. According to the raters' evaluations, 39 (62.9%) were classified as having motor fluctuations, while according to the UPDRS-IV 47 (75.8%) presented a motor fluctuation giving a sensitivity of 87.2% (95%CI 72.6–95.7) and a specificity of 43.5% (95%CI 23.2–65.5). Conclusion: Our study results confirm the high level of sensitivity with a lower level of specificity of UPDRS-IV to screen motor fluctuations in PD patients. Highlights: We performed a prolonged ambulatory monitoring of PD patients motor condition to objectively detect motor fluctuations. Six blinded raters classified patients as having or not motor fluctuations based on graphical reports of motor scores. We evaluated UPDRS-IV sensitivity and specificity using a 12-h waking-day motor assessment as gold standard. A high sensitivity (87.2%) with a low specificity (43.5%) of UPDRS-IV to screen motor fluctuations in PD patients was found.